Covid-19 and Spousal Violence against Women in Pakistan: A Web based Cross Sectional Study on Financial Anxieties and Rising Levels of Intimate Partner Violence during the Pandemic - Kiran Shehzadi, Iram Rubab, Ayesha Jabeen, Usman Javed Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Spousal violence against women has emerged as a ‘Shadow Pandemic’ during these times (Covid-19).This study was designed to investigate the interplay of socio-demographic factors and economic distress with spousal violence during the lockdown in Pakistan. Methods: A web based cross-sectional study was carried out to test the assumptions. 200 participants (100 women and 100 men) were selected through snowball sampling technique. A questionnaire containing demographic information, a composite abuse scale, and financial stress scale were adapted. Data was collected through Google Forms. Results: The results of Pearson Product Moment Correlation analysis revealed a significant positive relationship among partner violence against women, financial anxiety (r=.60, p<0.001), job insecurity (r=.48, p<0.001), and preserving of financial wellbeing (r=.32, p<0.001). Hierarchal Regression analysis revealed that financial anxiety and efforts to maintain financial wellbeing to be positive predictors of partner violence against women. The results of the study revealed maintaining financial wellbeing to be a significant positive mediator between partner violence and financial anxiety; whereas, life satisfaction was found to be a non-significant mediator. Conclusion: The findings of the study conclude that financial anxiety and assuring financial wellbeing tend to increase partner violence during pandemics and beyond.